A Structure-Conduct-Performance Analysis Of Commercial Air Transportation Industry In Indonesia - Dinarjito, Agung (Politeknik Keuangan Negara STAN, 2023)
To project the performance of an industry and a company, the market structure is one of the things that needs to be looked at. In addition, company behavior in the form of various strategies to increase customers also needs to be analyzed. Past performance will also be used to project industry and company performance. This research is descriptive research that aims to analyze the structure, behavior, and performance of the air transportation industry in Indonesia. The data used is secondary data and is limited to national airlines and the data used is also for domestic flight services in 2016-2020. Data were analyzed using a quantitative approach in the form of certain formulas, such as CR4, MES, and IHH. The results of the analysis conclude that the Indonesian commercial air transportation industry is in the form of a tight oligopoly or a dominant company with a competitive fringe. The behavior of national airlines in attracting consumers is carried out through various strategies, such as cooperating with other parties in marketing, providing onboard service strategies, and increasing timeliness. The performance of the aviation industry in 2016-2018 tends to increase. However, in 2019 and 2020 it tends to decrease. This can also be seen from the growth in passengers for each airline. In terms of load factor, Garuda and City Link experienced a significant decline from 2019 to 2020.